Amplifying Classroom Enjoyment and Cultivating Positive Learning Attitudes among ESL Learners - Ramzan, Muhammad; Javaid, Zartashia Kynat; Kareem, Abida; Mobeen, Sidra (Pakistan Journal of Humanities and Social Sciences, 2023)
Classroom environment and attitudes of students towards learning are core areas of interest to understand psychology of students. It helps teachers as well to make learning experience better. This study investigates the relationship between classroom enjoyment and English as a second language (ESL) students’ attitudes towards learning English. The research aims to shed light on the extent of enjoyment experienced by students in their learning environments and its impact on their attitudes towards learning English. A quantitative research design was employed, and data was collected through questionnaires administered to ESL secondary school students in Multan. The findings of the study indicate that ESL students generally experience a moderate level of enjoyment in their learning environments. This suggests that their learning environments are successful in fostering a sense of enjoyment. Furthermore, a significant relationship was found between classroom enjoyment and students' attitudes towards learning English, highlighting the importance of creating an enjoyable learning environment. The study emphasizes the role of learner-centered approaches, a supportive classroom environment, positive teacher-student relationships, and the integration of technology and authentic materials in promoting classroom enjoyment and positive learning attitudes among ESL students. These factors contribute to the creation of engaging and enjoyable learning experiences for ESL learners. The implications of this study are significant for educators, psychologists and curriculum developers. By prioritizing classroom enjoyment and creating positive learning environments, educators can enhance students' attitudes towards learning English and promote their motivation and engagement. Incorporating learner-centered approaches, utilizing authentic materials, and fostering positive teacher-student relationships are effective strategies to cultivate enjoyment and positive learning attitudes among students.